Ensuring Safe Transfusion Practices through Haemovigilance: India vis-a-vis Global Scenario - Rana, Ruhi; Veluri Kishore, Sastha R.; Kaur, Gagandeep; Singh, Gurvinder; Kumar, Rajesh (Current Drug Safety, 2023)
Haemovigilance is the monitoring of the essential components of blood transfusion from its initial stages to the final outcome considering all the safety parameters and hazards that co-exist with it. It primarily aims to ensure the quality as well as safety related to the use of blood and blood products utilizing the standard healthcare framework and a tailored vigilance program for efficient outcomes. Initially, the art of vigilance was started with the therapeutic products available in the market giving some groundbreaking data on their safety which later led to the implementation of timely measures to control adverse events significantly. Several incidents have occurred during the collection, transport, storage, and transfusion of blood and to stop these incidences of hazard, haemovigilance came into existence with France becoming the first country to step in followed by several nations across the world with customized guidelines directing it to the best. The majorly reported problems include bacterial infections, hemolytic and immune reactions. The present writeup reviews the inception and development of haemovigilance programs with a global scenario, a detailed study of the haemovigilance program adopted in India, and the updated status of these programs in various countries across the globe.
Keywords: Haemovigilance